2021
DOI: 10.1111/dom.14536
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of oral semaglutide in Japanese patients with type 2 diabetes: A post hoc subgroup analysis of the PIONEER 1, 3, 4 and 8 trials

Abstract: Aims: To evaluate, through exploratory post hoc subgroup analyses, the efficacy and safety of oral semaglutide versus comparators in Japanese patients enrolled in the global PIONEER 1, 3, 4 and 8 clinical trials.Materials and Methods: Patients were randomized to once-daily oral semaglutide 3, 7 or 14 mg or comparator (placebo, sitagliptin 100 mg or liraglutide 1.8 mg).Change from baseline in glycated haemoglobin (HbA1c) and body weight, and proportions of patients attaining HbA1c <7.0% (53 mmol/mol) and body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(134 reference statements)
1
7
0
1
Order By: Relevance
“…9 However, both the overall and gastrointestinal safety profiles of danuglipron are generally consistent with those described for peptidic GLP-1R agonists, 10,11 including the recent oral formulation of semaglutide. [12][13][14][15] In this study, increases in heart rate were observed in danuglipron dose groups after 8 weeks of dosing, which was observed in the previous study in Western participants 8 and in other studies with peptidic GLP-1R agonists. 16 The magnitude of heart-rate increases observed in this study is in line with short-term clinical data published with peptidic GLP-1R agonists.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…9 However, both the overall and gastrointestinal safety profiles of danuglipron are generally consistent with those described for peptidic GLP-1R agonists, 10,11 including the recent oral formulation of semaglutide. [12][13][14][15] In this study, increases in heart rate were observed in danuglipron dose groups after 8 weeks of dosing, which was observed in the previous study in Western participants 8 and in other studies with peptidic GLP-1R agonists. 16 The magnitude of heart-rate increases observed in this study is in line with short-term clinical data published with peptidic GLP-1R agonists.…”
Section: Discussionsupporting
confidence: 84%
“…More gradual dose‐escalation schemes over longer treatment durations are anticipated to result in lower incidence rates of gastrointestinal AEs 9 . However, both the overall and gastrointestinal safety profiles of danuglipron are generally consistent with those described for peptidic GLP‐1R agonists, 10,11 including the recent oral formulation of semaglutide 12‐15 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The greater treatment effects of semaglutide on HbA 1c and bodyweight could be due to differences in the pathophysiology of type 2 diabetes and genetic architecture in East Asian populations compared with those of Western populations 1 , 2 , 3 , 4 , 14 . For example, the presence of variants in diabetes‐associated loci that are unique to Japanese persons vs Europeans could be linked to differential effects on type 2 diabetes pathways between populations 15 .…”
Section: Discussionmentioning
confidence: 99%
“…The once‐daily oral formulation of semaglutide is also approved for type 2 diabetes treatment in Japan 19 , and the efficacy and safety of oral semaglutide in Japanese patients with type 2 diabetes have been investigated in a post‐hoc subgroup analysis of the PIONEER 1, 3, 4 and 8 clinical trials 14 . Similar to the results of our analysis of once‐weekly subcutaneous semaglutide, once‐daily oral semaglutide 3, 7 or 14 mg was found to be efficacious and well tolerated in Japanese participants 14 . Change from baseline to week 26 in HbA 1c was −1.0 to −1.2% points and −1.4 to −1.7%‐points for oral semaglutide 7 mg and 14 mg, respectively.…”
Section: Discussionmentioning
confidence: 99%